Design and performance of a compact forward-coupled HTS microstrip filter for a GSM system. - Guoyong Zhang
A practical design technique for a compact forward-coupled microstrip bandpass filter structure is introduced based on a computer-aided simulation and optimization software TUMIC. The structure consists of a parallel array of fully aligned half-wavelength resonators. Aimed at the application in the front-end receiver of a GSM base station, a 9-pole high-temperature superconductor filter with 2.6% fractional bandwidth at 1732.5 MHz was designed and fabricated using double-sided YBCO thin films on a 30-mm×30-mm×0.5-mm LaAlO3 wafer. The S-parameter measurements show a good agreement with the simulated results. At 30 K, the filter has less than 0.4-dB insertion loss, 0.3-dB passband ripple, and better than 12-dB return loss.
Keywords: 0.4 dB; 12 dB; 1732.5 MHz; 30 K; 9-pole high-temperature superconductor filter; GSM base station; GSM system; S-parameter measurements; TUMIC; Compact forward-coupled HTS microstrip filter; Computer-aided optimization software; Computer-aided simulation software; Design technique; Double-sided YBCO thin films; Forward-coupled microstrip bandpass filter structure; Fractional bandwidth; Front-end receiver; Fully aligned half-wavelength resonators; Insertion loss; Parallel array; Passband ripple; Return loss; LaAlO3.; LaAlO3 wafer; YBa2Cu3O7.